Profile of the elderly resident of the rural area and the use of medicines (Research, Society and Development, 2020)
Objectives: To profile elderly people living in the rural area of ​​a municipality in the extreme south of Rio Grande do Sul and to identify the use of potentially inappropriate medications. Methods: documentary, exploratory, descriptive study, with a quantitative approach, carried out in five Family Health Strategy Units. The collection was carried out in 180 medical records. Results: there was a prevalence of females, aged between 60 and 69 years, married civil status, literate and retired individuals. Systemic Arterial Hypertension was identified, followed by Diabetes Mellitus, Anxiety/Depression, Heart Diseases, and Chronic Obstructive Pulmonary Disease. As for the number of prescriptions, 71.1% of them had one or more medications potentially inappropriate for the elderly. Conclusions: It is believed that from the study it is possible to reflect on changes to improve care in primary care for the elderly, aiming at the practice of a safe therapeutic regime for this population, influencing the quality of life of the elderly with chronic disease .